New finding of Iris pineticola Klok. (Iridaceae) in the Ukraine Left Bank Forest-Steppe territory (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
A new locality of the rare endemic species Iris pineticola (Iridaceae) is described in the Left Bank Forest Steppe of Ukraine, in the Sula River basin near the border of the Lower Sula National Nature Park. Iris pineticola grows on an old clearing in the middle of an old floodplain forest on turfed alluvial light sandy soils in an ecotonic character grass community with diagnostic species of Molinio-Arrhenatheretea and Trifolio-Geranietea sanguinei classes, which is atypical. The location are given in the pine forests, artificial pine plantations on sandy river terraces in community of Pulsatillo-Pinetea classes, or on open sands in community of Festucetea vaginatae classes for the other known populations. Six-year monitoring has demonstrated the negative dynamics of the I. rineticola cenopulation: a decrease in numbers by 90%, the number of curtains (clones) by 60%, and the area by more than 80%. The cenopopulation consists only from 22 specimens, located by two curtains, 1 m2 total area for today. The age spectra analysis showed a predominance of immatures and virgins, which indicates a decrease in vegetative reproduction rates and the loss of self-support, fast degradation and probable disappearance in this locality in a short term. Degeneration of the population has obviously occurred as a result of an increase in soil coverage, due to the growth of projective coverage gramineas, and also partly due to plant damage facultative phytopathogenic fungi, causing alternariosis of pregenerative and generative specimens leaves. The ascomycete from Alternaria alternata complex, ribotype of which is common in Southeast, South and Asia Minor, the northern line of which runs along the 50 parallel of Europe is the causative agent of I. pineticola alternariosis. The locality we identified is the northernmost known point of the Alternaria alternata complex area, where the carrier of this ribotype was found on I. pineticola, where the defeat of I. pineticola by Alternaria alternata complex fungi and alternariosis Iridaceae was registered for the first time. Therefore, the I. pineticola local population needs conservation and inclusion of the territory with the identified location to the Nature Reserve Fund of Ukraine, in particular, Lower Sula National Nature Park, which will cause the implementation of organizational, legal, economic, scientific and other measures aimed at ensuring its protection and reproduction.
Keywords: Alternaria, coenopopulation, community, ecotone, ITS1, ITS2, phytopathogenic fungi, pine terrace.